2009
DOI: 10.1039/b913487e
|View full text |Cite
|
Sign up to set email alerts
|

Selective oxidative demethylation of veratric acid to vanillic acid by CYP199A4 from Rhodopseudomonas palustris HaA2

Abstract: CYP199A4 (RPB3613) from Rhodopseudomonas palustris HaA2 is a heme monooxygenase that catalyzes the hydroxylation of para-substituted benzoic acids. Monooxygenase activity of CYP199A4 can be reconstituted in a Class I electron transfer chain with an associated [2Fe-2S] ferredoxin, HaPux, (RPB3614) and the flavin-dependent reductase, HaPuR, (RPB3656) that is not associated with a CYP gene. CYP199A4 and the ferredoxin HaPux are produced in greater quantities using recombinant Escherichia coli expression systems w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
163
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 68 publications
(165 citation statements)
references
References 35 publications
(45 reference statements)
2
163
0
Order By: Relevance
“…The first electron transfer is rate limiting for a number of bacterial P450 systems including P450 cam (CYP101A1) from Pseudomonas putida (Brewer and Peterson, 1988), CYP199A2 and CYP199A4 from Rhodopseudomonas palustris (Bell et al, 2010b(Bell et al, , 2010c) and CYP101D1 from Novosphingobium aromaticivorans Bell et al, 2010a;Yang et al, 2010). It has been shown that the first flavin-to-heme electron transfer, though one of the slower steps in the overall catalytic cycle, is not rate limiting for palmitate and arachidonate oxidation by P450 BM3 (Munro et al, 1996;Ost et al, 2003;Whitehouse et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The first electron transfer is rate limiting for a number of bacterial P450 systems including P450 cam (CYP101A1) from Pseudomonas putida (Brewer and Peterson, 1988), CYP199A2 and CYP199A4 from Rhodopseudomonas palustris (Bell et al, 2010b(Bell et al, , 2010c) and CYP101D1 from Novosphingobium aromaticivorans Bell et al, 2010a;Yang et al, 2010). It has been shown that the first flavin-to-heme electron transfer, though one of the slower steps in the overall catalytic cycle, is not rate limiting for palmitate and arachidonate oxidation by P450 BM3 (Munro et al, 1996;Ost et al, 2003;Whitehouse et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…[1,15,16] For example, 4-ethylbenzoic acid is efficiently hydroxylated and desaturated by CYP199A4 to yield 4-(1-hydroxyethyl)-and 4-vinyl-benzoic acid, respectively. [1] The closely related CYP199A2 enzyme, from the CGA009 strain of R. palustris, has been reported to be a biocatalyst for the oxyfunctionalisation of 4-methoxybenzoic acid and various other aromatic carboxylic acids including 2-naphthoic, indole-6-carboxylic and cinnamic acids. [7,[17][18][19][20] Recently, the wild-type enzyme and mutant forms of CYP199A2…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…[14][15][16] For instance, CYP199A4 can bind and O-demethylate 2,4-and 3,4-dimethoxybenzoic acids with total regioselectivity at the 4-methoxy group to yield 2-methoxy-and 3-methoxy-4-hydroxybenzoic acids, respectively. [1,16] CYP199A4 has also…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations